2014
DOI: 10.1007/s10126-014-9578-8
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTLs for Swimming Ability Related Traits in Cyprinus carpio L.

Abstract: Body height (BH), head length (HL), snout length (SL), and tail length (TL) are important traits related with swimming ability of fish. Therefore, improving these traits will increase the production which is the basic goal of aquaculture breeding. To understand the genetic basis of swimming ability related traits in Cyprinus carpio L., a high-density linkage map spanning 3,301 cM in 50 linkage groups was utilized for quantitative trait locus (QTL) mapping. Mapping family comprised 190 offspring and 627 molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Growth-related traits (e.g., body weight and length) constitute the main purpose of genetic breeding projects in aquaculture. Earlier studies on common carp have confirmed a heritable basis in these traits [ 37 ], and some QTLs affecting growth-related traits have been reported [ 32 35 , 38 , 39 ]. For example, Laghari et al [ 32 ] performed analysis looking for BW, TL, and condition factor (K) based on a backcross common carp family, they detected 12 QTLs associated with BW and TL on ten LGs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Growth-related traits (e.g., body weight and length) constitute the main purpose of genetic breeding projects in aquaculture. Earlier studies on common carp have confirmed a heritable basis in these traits [ 37 ], and some QTLs affecting growth-related traits have been reported [ 32 35 , 38 , 39 ]. For example, Laghari et al [ 32 ] performed analysis looking for BW, TL, and condition factor (K) based on a backcross common carp family, they detected 12 QTLs associated with BW and TL on ten LGs.…”
Section: Discussionmentioning
confidence: 96%
“…Another significant QTL (chromosome-wide P < 0.01) for TL on LG13 in F234, also had an overlapping QTL region with that associated with SL reported by Zheng et al [ 38 ]. Additionally, one QTL for BW on LG30 in F259 was identified as having a shared region with the QTL for body height (qBH30) on this chromosome in an F 1 population [ 39 ]. Other than these examples, there are no other reports of overlap in the literature on QTL mapping for common carp growth traits.…”
Section: Discussionmentioning
confidence: 99%
“…Construction of the high-resolution map for the Yangtze River strain of common carp would provide more information to understand the genome structure and gene rearrangement between the two subspecies. QTLs for growth-related traits have been identified by several studies in the Songpu mirror carp strain mainly based on microsatellite markers [ 36 38 ]. Compared with SNPs, microsatellites have longer flanking DNA sequences which are effective for comparative mapping.…”
Section: Introductionmentioning
confidence: 99%
“…Two overlapping QTL regions were discovered. One affecting PAUC on LG30 was found to have an overlapping QTL interval with that associated with BH on this LG in an F1 population (Laghari et al, 2014b). The other one located at 0-7 cM on LG13 was affecting 10 morphometric traits (ADPA, ADPD, ANAD, PVAD, PSAN, ANPA, PTPV, PVPS, SNCP and LCUC) in the SP analysis, which have a common QTL region with that associated with SL reported by Zheng et al .…”
Section: Qtl Detectionmentioning
confidence: 50%
“…Genetic studies aiming to identify loci controlling morphological variation have been carried out in three-spine stickleback (Gasterosteus aculeatus) (Liu et al, 2014;Yang et al, 2016), Whitefish (Coregonus clupeaformis) (Laporte et al, 2015), gilthead seabream (Sparus aurata) (Boulton et al, 2011;Loukovitis et al, 2013), and European sea bass (Dicentrarchus labrax) (Chatziplis et al, 2007;Massault et al, 2010). However, QTL mapping relating to the morphological performance of common carp only involved standard length (SL), body height (BH), head length, tail length and so on Laghari et al, 2014b;Lu et al, 2015). Thus, our study is aimed at examining the genetic architecture of morphometric traits in common carp, and detecting major loci affecting these traits.…”
Section: Introductionmentioning
confidence: 99%